Pengaruh Komitmen Organisasi dan Kepuasan Kerja Terhadap Efektivitas Organisasi dengan Organizational Citizenship Behavior sebagai Variabel Intervening (Studi Kasus pada Sekretariat Badan Penyuluhan dan Pengembangan SDM Pertanian Kementerian Pertanian) - Daliman . (JURNAL CITRA WIDYA EDUKASI, 2016)
The purpose of this study was to assess the influence of Organizational Commitment (X1) and Job Satisfaction (X2) on Organizational Effectiveness (Y) using Organizational Citizenship Behavior (Z) as an intervening variable. The model used in this study is a model of causality or influence relationships. To examine the hypotheses proposed in this study, the analysis technique used is the path analysis. After testing and data analysis to test hypotheses proposed, this study offers the following conclusions: 1) the Organizational Commitment (X1) has smaller effect than the variable influence Job Satisfaction (X2) on Organizational Effectiveness (Y); 2) through Organizational Citizenship Behavior (Z), Organizational Commitment (X1) has smaller effect compare Job Satisfaction (X2) on Organizational Effectiveness (Y); and 3) Organizational Citizenship Behavior (Z) has a direct impact on the Organizational Effectiveness (Y).